2008
DOI: 10.1152/ajpregu.90560.2008
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of the transcriptome of the subfornical organ in the rat: regulation by fluid and food deprivation

Abstract: We have employed microarray technology using Affymetrix 230 2.0 genome chips to initially catalog the transcriptome of the subfornical organ (SFO) under control conditions and to also evaluate the changes (common and differential) in gene expression induced by the challenges of fluid and food deprivation. We have identified a total of 17,293 genes tagged as present in one of our three experimental conditions, transcripts, which were then used as the basis for further filtering and statistical analysis. In tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
59
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 57 publications
8
59
1
Order By: Relevance
“…25). These results confirm and extend recent findings of gene array studies from our laboratory, demonstrating the presence of leptin receptor mRNA in the SFO (20). In the present study, we sought to identify whether the mRNA was translated into a functional receptor using two approaches: 1) immunohistochemistry for the receptor and 2) leptin-induced activation of STAT3, revealed as nuclear labeling of pSTAT3 immunoreactivity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…25). These results confirm and extend recent findings of gene array studies from our laboratory, demonstrating the presence of leptin receptor mRNA in the SFO (20). In the present study, we sought to identify whether the mRNA was translated into a functional receptor using two approaches: 1) immunohistochemistry for the receptor and 2) leptin-induced activation of STAT3, revealed as nuclear labeling of pSTAT3 immunoreactivity.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, recent gene array studies from our own laboratory have revealed the presence of the leptin receptor mRNA in the SFO (20). The present study was undertaken to test the hypothesis that leptin signaling occurs in the SFO.…”
mentioning
confidence: 97%
“…Studies show that various physical stress procedures such as water and food deprivation, exposure to cold, hypotension, hypertonic extracellular volume expansion, lipopolysaccharide treatment regulate CART expression in the brain [48][49][50][51][52] . Studies demonstrate that psychological stress also changes CART peptide and mRNA expression in the hypothalamus, limbic areas, brainstem and the adrenal gland.…”
Section: Cart and Stressmentioning
confidence: 99%
“…The AP is probably not unique in this regard because the SFO also has a similar assortment of diverse channels and peptide receptors (16). The OVLT has not yet been analyzed in this manner.…”
mentioning
confidence: 99%
“…The gene chip studies have added a great amount of information to our understanding of the CVOs, but they have implicitly assumed that the CVOs are homogenous structures (16,17), and clearly, this is not the case. Each CVO has its own defined cytoarchitectonic regions and contains a heterogeneous group of neurons (24).…”
mentioning
confidence: 99%